2014
DOI: 10.1111/jir.12175
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of behavioural activation for depressive symptoms in adults with intellectual disabilities

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 31 publications
2
51
0
5
Order By: Relevance
“…For example, participants in previous research have constructed challenging behaviour as a response to negative relationships (Duperouzel & Fish, ; Fish & Culshaw, ) or as a response to internal mental distress (Brown & Beail, ). Findings around feelings of loss, sadness or anxiety precipitating aggressive behaviour are also consistent with recent research demonstrating that referrals for aggression often mask an underlying depression in people with learning disabilities (Jahoda et al, ; Willner et al, ). Previous research has also identified the potential benefits of service users holding perceptions of greater personal control over their challenging behaviour (Hawkins, Allen, & Jenkins, ; Ruef & Turnbull, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, participants in previous research have constructed challenging behaviour as a response to negative relationships (Duperouzel & Fish, ; Fish & Culshaw, ) or as a response to internal mental distress (Brown & Beail, ). Findings around feelings of loss, sadness or anxiety precipitating aggressive behaviour are also consistent with recent research demonstrating that referrals for aggression often mask an underlying depression in people with learning disabilities (Jahoda et al, ; Willner et al, ). Previous research has also identified the potential benefits of service users holding perceptions of greater personal control over their challenging behaviour (Hawkins, Allen, & Jenkins, ; Ruef & Turnbull, ).…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, a restricted ability to exert choice and engage with meaningful activity promoted boredom and frustration, decreasing this coping ability. These processes are consistent with theories highlighting the role of disempowering environments in promoting “learned helplessness” (DeVellis, ; Foy & Mitchell, ; Kahana, Kahana, & Riley, ; Seligman, )and the role of meaningful activity in building positive mood (Jahoda et al, ; Jahoda et al, ). There is of course a need to balance increasing power and control with adequate risk management and meeting an individual's support needs—a collaborative risk management process was identified in this study as a means of bridging this gap.…”
Section: Discussionsupporting
confidence: 85%
“…A small non‐randomised feasibility study suggested that behavioural activation may have efficacy in treating depression (Jahoda et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; Jahoda et al . ). Such approaches may complement, rather than replace inputs that address the unique life experiences of people with ID, often marked by discrimination and exclusion (Jahoda et al ., ) and promote meaningful activities and social inclusion.…”
Section: Discussionmentioning
confidence: 97%
“…After all, IAPT uses talking therapies almost exclusively, and many people with ID do not communicate verbally. However, IAPT staff have skills in preventative and mental health promotion approaches, areas that have been neglected in ID research and practice (Dagnan 2008) and in using the behavioural techniques in CBT, which could be shared very effectively with ID staff interested in facilitating CBT interventions with people with ID (Dodd et al 2013;Jahoda et al 2015). Such approaches may complement, rather than replace inputs that address the unique life experiences of people with ID, often marked by discrimination and exclusion (Jahoda et al, 2006) and promote meaningful activities and social inclusion.…”
Section: Discussionmentioning
confidence: 99%